Neurodevelopmental outcome in meningococcal disease: a case–control study. Issue 1 (1st July 2001) - Fellick, J M; Sills, J A; Marzouk, O; Hart, C A; Cooke, R W I; Thomson, A P J
Abstract : AIMS: To determine long term neurodevelopmental outcome following the spectrum of meningococcal infection. METHODS: Between 1988 and 1990, 152 cases of meningococcal disease were recruited; 139 survived. Between 1998 and 1999, 115 survivors (83%) were evaluated, together with 115 sex and age matched controls. Standard measures of neurological function, coordination, cognition, behaviour, and hearing were used to assess neurodevelopmental status. RESULTS: One case has spastic quadriplegia. Gross neurological examination was normal in all other cases and all controls. Five cases and no controls have significant hearing loss. Cases performed at a lower level than controls on measures of coordination, cognition, and behaviour. Four cases and no controls had major impairments. The adjusted odds ratios for moderate and minor impairments were 3.6 (95% CI 1.3 to 10.3) and 1.6 (95% CI 0.8 to 3.4) respectively. CONCLUSION: The majority of survivors from this cohort do not have gross neurological deficits. However, when objective measures of motor function, cognitive ability, and behaviour were applied significant detriments were found in meningococcal survivors.